ENGLISH LANGUAGE COMPETENCE OF BASIC EDUCATION TEACHERS IN A PRIVATE SCHOOL - Kristine Mae Auayang (CV. ADIBA AISHA AMIRA, 2025)
Language competence is required among teachers for effective professional practice because they use language as a medium and object of instruction. This study aimed to determine the private basic education teachers' language competence. A mixed method was utilized to gather data. The study revealed that basic education teachers have an overall basic level of language competence. It is attributed to insufficient knowledge of grammatical rules, amount of workload, lack of awareness about the language’s social rules, lack of seminars and training for professional development, use of code-switching, weak foundation on sensitivity, culture, behavior, and non–verbal communication, and anxiety in using English. Furthermore, English teachers and those who have higher educational attainment have an advanced level of overall language competence, while teachers who have longer years in teaching and those who have high educational attainment have an advanced level of sociolinguistic and strategic competence respectively. This implies that teachers who do not specialize in English, who are new in the teaching profession, and who are holders of bachelor's degree must undergo more training and seminars to intensify their competence in language; hence, there is a necessity to propose and implement a differentiated developmental program